Book Review of Cook-Cottone’s Embodiment and the Treatment of Eating Disorders: The Body as a Resource in Recovery - Nutter, Sarah (Canadian Journal of Counselling and Psychotherapy, 2021)
Embodiment and the Treatment of Eating Disorders: The Body as a Resource in Recovery by Catherine Cook-Cottone provides over its 13 chapters a theoretical framework and practice recommendations for infusing embodiment in eating disorder treatment via her Embodied Approach to Treating Eating Disorders model. Part 1 of the book provides an overview of the model and Part 2 provides a framework for integrating the model into treatment, using several aspects of embodiment. Cook-Cottone includes numerous resources in the book to support counsellors in integrating this model into practice. For clinicians working with clients struggling with disordered eating or eating disorders, Cook-Cottone’s book provides an engaging addition to eating disorders treatment.